Tendințe în cercetarea RAM: O perspectivă bibliometrică asupra păsărilor domestice vs. sălbatice (2015–2025) - Daiana ionela Cocoș; Mihai Folescu; Larisa Maria Ardelean; Caius Stoichescu; Eugenia Dumitrescu; Romeo Teodor Cristina (Medicamentul Veterinar)
Antimicrobial resistance (AMR) in Enterobacteriaceae remains a critical challenge for both public and veterinary health, driven by intensive antibiotic use in poultry production and the natural dissemination of resistant bacteria via wildlife. This study aimed to perform a comparative bibliometric analysis of scientific literature on AMR in domestic (poultry) and wild birds, using PubMed data from 2015 to 2025. The results revealed a markedly higher number of publications focusing on poultry, predominantly from Asia and Western Europe. In contrast, studies on wild birds were fewer but exhibited greater methodological diversity, incorporating advanced techniques such as metagenomics and 16S rRNA sequencing. MeSH term analysis highlighted thematic differences: poultry-related articles emphasized zoonotic risks and food production, whereas studies on wild birds focused on ecological surveillance. These findings underscore the need to integrate wild birds into AMR monitoring frameworks as part of a holistic One Health approach.